Intervensi Spiritual untuk Meningkatkan Kesejahteraan Spiritual Pasien Kanker - Rohmawati, Dwi Asih; Afiyanti, Yati; Pujasari, Hening (Journal of Telenursing (JOTING), 2024)
This study aimed to explore and synthesize the scientific literature on the types of spiritual interventions that are effective in improving spiritual wellbeing in cancer patients. The method used was a systematic review through the PubMed, Science Direct, EBSCOhost and Springer Link databases using the keywords: cancer patients OR oncology patients OR patients with cancer AND spiritual interventions AND spiritual well being OR spiritual health OR spiritual healing, with inclusion criteria for cancer patients aged >18 years, January 2010 - September 2023 the selection process used the PRISMA method and the quality assessment of articles using the JBI tools RCT design. The number of initial search articles was 6725 articles with 13 articles used. The results showed that 8 spiritual interventions were found to be statistically effective in improving the mean spiritual well-being score in cancer patients. Conclusion spiritual interventions can be effective in improving spiritual well-being in cancer patients who have metastases and are in palliative care as well as those with chemotherapy. Keywords: Spiritual Interventions, Cancer Patients, Spiritual Well-Being